When Liquidity and Governance Shape Firm Value: Evidence from Indonesia’s Consumer Non-Cyclicals Sector - Endraria Endraria; Yusar Sagara (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Firm value represents a key indicator of business performance and market confidence, particularly in emerging economies where structural and governance dynamics play crucial roles. This study aims to examine the effect of capital structure, firm size, and profitability on firm value while considering liquidity and corporate governance as moderating variables. The sample consists of 15 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2020–2024, yielding 75 observations. Panel data regression with the Fixed Effect Model was employed after conducting Chow, Hausman, and Lagrange Multiplier tests. The results reveal that capital structure (DER) has a significant positive effect on firm value (PBV), whereas firm size shows a significant negative effect in a specific model. Profitability (ROA), liquidity (CR), and corporate governance (GCG) have no significant direct impact on firm value. However, GCG significantly moderates the relationship between firm size and PBV in a positive direction, while other moderating effects are not significant. These findings reinforce the trade-off theory and agency theory, while also providing practical implications for managers, investors, and policymakers in making strategic decisions.